2014
DOI: 10.1017/s1598240800008912
|View full text |Cite
|
Sign up to set email alerts
|

Language Stereotypes in Contemporary Taiwan: Evidence from an Experimental Study

Abstract: We collected original experimental data, using the matched-guise technique, to examine the Taiwanese people's evaluational reactions to two major spoken languages in contemporary Taiwan: Mandarin and Taiwanese. Taking advantage of the effectiveness of the experimental technique in controlling for possible unobserved confounding variables, we clearly and systematically demonstrate that (1) language stereotypes do exist in today's Taiwan, and (2) there are some serious and significant implications for Taiwan's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…On the one hand, the failure to date to reach consensus on an orthographic representation weighs heavily on the continued lack of progress in normalizing its use. This factor is only one among a broader array of adverse conditions (only a small percentage of young Taiwanese today do not speak Mandarin, the other autochthonous languages have received official recognition since democratization and vie for preservation); see and Chang and Lu (2014), Dupré (2014) and Liu (2012). Nevertheless, such language status deficits and sociolinguistic imbalances that strongly tip the balance in favor of Mandarin have no effect, one way or the other, on the proposal to categorize Minnan as a language, even in the hypothetical case of future advanced erosion.…”
Section: Why Is This Discussion Important For the Field Of Bilingualimentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the failure to date to reach consensus on an orthographic representation weighs heavily on the continued lack of progress in normalizing its use. This factor is only one among a broader array of adverse conditions (only a small percentage of young Taiwanese today do not speak Mandarin, the other autochthonous languages have received official recognition since democratization and vie for preservation); see and Chang and Lu (2014), Dupré (2014) and Liu (2012). Nevertheless, such language status deficits and sociolinguistic imbalances that strongly tip the balance in favor of Mandarin have no effect, one way or the other, on the proposal to categorize Minnan as a language, even in the hypothetical case of future advanced erosion.…”
Section: Why Is This Discussion Important For the Field Of Bilingualimentioning
confidence: 99%
“…Recall that Putonghua is based on Modern Standard Mandarin, one of the Chinese languages, according to the standard method. For comparison, if we categorize Yue, Mandarin, Minnan, Wu and Hakka as dialects of Chinese, the same approach within the Indo-European family would group Italian, Spanish, Portuguese, Catalan and Romanian as dialects of "Romance"; for discussion, see Cheung and Bauer (2002), Matthews and Yip (2011). Even in the case of the Romance languages, genetically and typologically very close, recent descendants from their parent, mutual intelligibility is nevertheless considerably restricted.…”
Section: Sino-tibetanmentioning
confidence: 99%
“…It was interesting to note that one teacher maintained that learners should not be penalised for using Khelobedu words because if they are marked wrong they might achieve poor grades. On the contrary Lu (2014), who argues that if learners are not marked wrong for incorrect vocabulary, this could cause confusion and impede the writing progress.…”
Section: Learner Challengesmentioning
confidence: 99%
“…Somewhere between these two political ideologies and preferences is the grey field where the Chinese government should focus its efforts into content management. Various surveys have shown that the majority of Area A themselves are in the middle point between these two extremes [24] .…”
Section: Reactive Sequence 2017mentioning
confidence: 99%